3(y+-4)+9(y+1)=

Simple and best practice solution for 3(y+-4)+9(y+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y+-4)+9(y+1)= equation:


Simplifying
3(y + -4) + 9(y + 1) = 0

Reorder the terms:
3(-4 + y) + 9(y + 1) = 0
(-4 * 3 + y * 3) + 9(y + 1) = 0
(-12 + 3y) + 9(y + 1) = 0

Reorder the terms:
-12 + 3y + 9(1 + y) = 0
-12 + 3y + (1 * 9 + y * 9) = 0
-12 + 3y + (9 + 9y) = 0

Reorder the terms:
-12 + 9 + 3y + 9y = 0

Combine like terms: -12 + 9 = -3
-3 + 3y + 9y = 0

Combine like terms: 3y + 9y = 12y
-3 + 12y = 0

Solving
-3 + 12y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 12y = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 12y = 0 + 3
12y = 0 + 3

Combine like terms: 0 + 3 = 3
12y = 3

Divide each side by '12'.
y = 0.25

Simplifying
y = 0.25

See similar equations:

| 11m^2-2m=10 | | 4(3+c)=3(c-4) | | 8n-6=10 | | 3t+15=13t | | 7(a+3)=4a | | 10m(4m-9)=30 | | y^2+8y=4 | | 8(w-6)=2w | | 2x-45=43-2 | | 6*(3x-7)-12-4x=9x-(7x+6) | | x-7-7x=5 | | 10u-20=9u-11 | | 3(a+2)=a+12 | | 8s^2-30s+18= | | 16m^2-1=15m | | 2x^2-25x+36=0 | | X^2-1x-1=0 | | 6a^2-19a+15= | | -6n+10=-4n-18 | | 7y-10=5y-2 | | -6x-9y=54 | | (9m^3+4n)+7m^3= | | 21-11=5(x-1) | | 8-9x=104-37x | | 6x-2=x-0 | | 6f-14+26-3f-15f= | | -6x+2=1 | | -121-8x=8x+23 | | y^2+3y-16=y-1 | | 3(y-2)=12 | | X^2+19x+K= | | -x=3+2x+16 |

Equations solver categories